Complexity from Simplicity: Unique Polymer Capsules, Rods, Monoliths, and Liquid Marbles Prepared via HIPE in Microfluidics. (27th February 2013) - Gokmen, M. Talha; Dereli, Busra; De Geest, Bruno G.; Du Prez, Filip E.
<x xml:space="preserve">Abstract</x> Existing methods for preparing complex particles, i.e., hollow porous, depend on either multiple steps or a complex reactor design. Here, a straightforward method to prepare unique polymer particles with complex shapes via the use of simple equipment and readily available chemicals is reported. Beads, capsules, and rods with uniform size and interconnected pores are obtained through the formation of high internal phase emulsion (HIPE) droplets in a microfluidic channel. The method is applicable to a broad range of (meth)acralates. Controlling physical properties, such as viscosity and emulsion stability, is key to control the shape of the resulting particles. Post‐modification of the particles via click chemistry, their application in liquid marble formation, and their use as droplet reactors are also demonstrated.